Comprehensive Management of Ectodermal Dysplasia with Interceptive Orthodontics in a Young Boy Who Was Bullied at School - A. A. A. K. Wimalarathna; W. B. M. C. R. D. Weerasekara; E. M. U. C. K. Herath (Case Reports in Dentistry)
Aim. The management of hypohidrotic ectodermal dysplasia with oligodontia in Class-I malocclusion in late mix dentition. Case Report. An 11-year-old boy with ED was treated and managed by means of interceptive orthodontic treatment accompanied by direct and indirect restorative methods in a successful manner. The patient was prepared to receive definitive oral rehabilitation with dental implants for the missing teeth when the patient reaches a suitable age. The patient was followed for 5 years from the beginning of treatment. Conclusion. Management of the child with ectodermal dysplasia with oligodontia was a real challenge. Early diagnosis, necessary investigation, and providing age-appropriate multidisciplinary treatment were key steps in successful outcomes. The objectives were not only just orthodontic or paedodontics but also prosthetic and psychological.